An Appraisal of Ffectiveness of Integrated Payroll and Personnel Information System (IPPIS) in Elimminating Ghost Workers in Nigerian Public Service - Danbala, Ibrahim Nuaimu; Suleiman, Engaya; Bala, Bashir (African Multidisciplinary Journal of Sciences and Artificial Intelligence, 2024)
The study, An Appraisal of Effectiveness of Integrated Payroll and Personnel Information System (IPPIS) In Eliminating Ghost Workers in Nigerian Public Service. The ghost worker’s syndrome has been worrisome situation across all tiers of government and has led to government spending billions of naira accounting for the money being syphoned through payment of non-existing employees. Therefore, this study examines the effects of ghost workers’ syndrome and how the instrumentality of integrated payroll and personnel information system (IPPIS) could address the menace in the public service. Its specific objectives were to determine the impacts of ghost workers’ fraud on irregular payment of salaries in the Nigerian public service, to understand the effectiveness of integrated payroll and personnel information system (IPPIS) in eliminating ghost workers in Nigerian public service. The data were analyzed using frequency counts and percentages, and Data generated from both Primary and Secondary Sources. The study adopted New Public Management Theory as its Theoretical Framework. The findings show that there is a significant relationship between ghost workers, fraud and irregular payment of salaries in Nigeria public service. The recommendations are to use biometric technology, the use of BVN and also punishing the perpetrators of the act. This study intends to provide explanation to the effectiveness of Bank Verification Number (BVN) in detecting and eliminating ghost workers in the Nigerian public service by appraising the Integrated Payroll and Personnel Information System (IPPIS).